The Effect of Work Engagement on Individual Work Performance in the Psychology in Happiness Perspective: Mediated by Happiness at Work - Wang, Jinzhan; Rahman, Azra Ayue Binti Abdul (International Review of Management and Marketing, 2026)
Due to the widespread use of electronic devices and digital technology, modern enterprises are paying increasing attention to the dedication of contemporary employees. This research aims to study the mediating role of happiness at work from a psychology in happiness perspective through the logic of social cognitive theory (SCT), and to address this critical gap in existing literature. The study used quantitative methods to collect sample data from 372 full-time employees. Empirical data analysis shows that happiness at work plays a significant mediating role in the effect of work engagement on individual work performance. There is also a significant correlation between these factors. The innovation of this research lies in the fact that t is one of the few empirical research works that incorporates the concept of happiness at work as a mediator into the field of human resource management. Based on empirical evidence, the theoretical model has been improved through research.